Catastrophic failure of cup revision hip arthroplasty due to undiagnosed Paget disease of bone: A case report. (2020) - Fukui, Kiyokazu; Kaneuji, Ayumi; Yonezawa, Katsutaka; Shioya, Akihiro; Ichiseki, Toru; Kawahara, Norio
Highlights: Paget disease of the bone, while exceptionally rare in Asian populations, may be responsible for the loosening of arthroplasty components. The correct diagnosis of Paget disease of the bone was delayed, resulting in the rapid destruction of the pelvic bone. It is advisable that older patients with suspicious bone lesions be further evaluated and that their serum alkaline phosphatase levels be measured. The use of preoperative antipagetic medication for reducing PDB activity should be considered. It may decrease the risk of implant loosening. Abstract: Introduction: Paget's disease of bone (PDB) is a localized chronic osteopathy, apparently not genetic in origin, and frequently diagnosed from incidental radiographic images. The disease is characterized by deformation, hypervascularity, and structural weakness of the bone and by changes in joint biomechanics. Most cases of PDB can be easily diagnosed from radiographic findings, but monostotic cases may be problematic and require invasive procedures. Presentation of case: A 70-year-old woman had re-revision surgery for early catastrophic failure of an isolated cup revision hip arthroplasty because of undiagnosed PDB 21 years after the primary total hip arthroplasty. To identify the pathomechanism of early failure, we performed bone biopsy on the right iliac crest. Histopathological findings showed a mosaic pattern in the bone characteristic of PDB. Prior to the planned re-revision surgery, we treated the PDB with denosumab until the patient's serum level of alkaline phosphatase (ALP) was within the normal limits. Two months after denosumab treatment, we performed re-revision hip arthroplasty using a structural allograft and a Kerboull-type reinforcement device. Discussion: The delay in correct diagnosis of PDB was associated with the rapid destruction of pelvic bone. The preoperative use of antipagetic medication could decrease the risk of implant loosening and may be warranted to mitigate that risk. Conclusion: In patients with a failed arthroplasty, thoughtful evaluation is warranted for preoperative antipagetic medication in order to reduce PDB activity and potentially decrease the risk of implant loosening. This paper offers some steps for such risk reduction in the workup before revision surgery.